Responses of enriched chicken b lymphocytes population towards infection of different genotypes of velogenic Newcastle disease virus - Teo, Kristeen Ye Wen; Omar, Abdul Rahman; Yeap, Swee Keong; Tan, Sheau Wei; Tan, Soon Guan; Mohammed Alitheen, Noorjahan Banu (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Newcastle disease (ND) is a major disease in poultry industry that caused high loss and mortality. Fundamental study on the virus-host interactions is needed to address the issue of repeated outbreaks of NDV in Asia. In this study, the effect of inflammatory stress on the viability toward the development of humoral immunity was investigated in chicken IgM+ B lymphocytes when infected with different genotypes of velogenic NDV. When infected with NDV genotype VII UPM/IBS/002/2011 and genotype VIII AF2240, reduction of IgM+ B lymphocytes population and infiltration of macrophage was observed in the chicken bursa of Fabricius. The increment of macrophage population subsequently resulted in the elevation of nitric oxide (NO) content in the infected chickens with AF2240 causing higher increment of NO compared to UPM/IBS/002/2011. In brief, both genotypes of NDV strains caused different immune response in chicken enriched B lymphocytes upon virus infection.